A NEW SPECIES OF CASSINE (CELASTRACEAE) FROM INDIA - Sasidharan, N.; Swarupanandan, K. (Research Center for Biology, 1992)
The new species Cassine kedarnathii Sasi. & Swarup. is described from the Silent Valley National Park (India) and illustrated.